Evolution of precipitates during creep deformation for alloy 718 - Chanhee Park; Joonho Lee; Woo-Sang Jung (Journal of Materials Research and Technology)
This study investigated the microstructural evolution of the γ′′, γ′, and δ phases during creep for alloy 718. Creep tests on two-step aged samples were conducted under different stresses and temperatures ranging from 600 to 700 °C. Analysis of precipitates was performed on two-step aged and crept samples using scanning electron microscopy and transmission electron microscopy. The creep rupture lives were decreased with increasing stresses and temperatures and showed a linear correlation between experimental data and Larson-Miller parameter curve predictions. The γ′′ phase was formed as a disc shape in the grain interior and had an orientation relationship of (001)γ′′//{001}γ and [100]γ′′//<100>γ with γ matrix. The length of the γ′′ phases increased with increasing temperatures and creep exposure time. The activation energy for γ′′ lengthening was 323 kJ/mol, similar to that for lattice diffusion of Nb in Ni. It was found that the formation mechanisms of δ phase were different from temperatures. The δ phase was formed in grain interiors and grain boundaries and had a blocky shape during a sub-δ solvus annealing process. On the other hand, the δ phase was formed as a plate shape and had an orientation relationship of (010)δ//(111¯)γ and [102]δ//[011]γ with γ matrix at creep temperatures. The growth rates of plate δ phase were faster than blocky δ phase at all creep temperatures.